Design and Simulation of Flexible Arms of Moxibustion Robots - Wang Xin; Hou Tengda (Jixie chuandong)
The flexible arm of moxibustion robots was designed and simulated, and the flexible arm was made of thermoplastic polyurethane (TPU) and segmented bellows, including the bending section and the elongated section. Using Abaqus CAE analysis software, the structural dimensions such as the wall thickness and the corrugated angle of the bellows were optimized, the kinematics simulation analysis of the flexible arm was carried out from the relation between bending angle and air pressure and flexibility, and the mechanical properties of the flexible arm were calculated and analyzed. The results show that the robot's flexible arms designed for the moxibustion application can meet the requirements of the load capacity and the flexibility.